The Paradox of Poverty: Exploring the Intersection of Online Loan Defaults and Corruption Among Low-Income Communities - Kurniawan, Reza; Triyadi, Rudini (Jogjakarta Communication Conference (JCC), 2025)
The rise of online lending platforms in Indonesia is accompanied by significant issues, one of which is the